Dry-Stone walls as touristic attractive. Comparative between northeast and southwest of Iberian Peninsula - Mallafrè Balsells, Cèlia (2022)
The promotion of dry-stone vernacular heritage as a pole of attraction of sustainable tourism has a key role on its preservation. Moreover, the outreach prevents the loss of the technique, since the knowledge becomes accessible for people. In the same way, this interest on vernacular heritage has a favourable impact on rural areas, where devalued and non-profitable terrains can be attractive for the society with new uses. Dry-stone technique only uses stones without other joining material. The shape and the appearance of those constructions varies from one place in function of various features. Based on the structural principles of dry-stone technique, they had to adapt to the material, the surroundings and the necessities. The methodology proposes the analysis of formal and structural differences and similarities of dry-stone walls located on different Iberian Peninsula areas. Three areas of study are chosen to perform the comparison: Northeast and Southwest of Iberian Peninsula. In the Northeast, the study is focused on the Terra Alta region (Spain) and, in the Southwest the study analyses the North of Seville region (Spain) and Algarve area (Portugal). This study evidences the differences and common features for the conservation of that heritage, which are common all over the world. Following, the study focuses on the context of conservation, dissemination and formation of this vernacular heritage, both in these specific areas and in the international context. Finally, a protocol is proposed to design promoting actions in the context of sustainable tourism linked to the dry-stone heritage.